2022
DOI: 10.3389/fchem.2022.1058229
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and evaluation of 3-alkynyl-5-aryl-7-aza-indoles as broad-spectrum antiviral agents

Abstract: RNA viral infections, including those caused by respiratory syncytial virus (RSV), severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), and Venezuelan Equine encephalitis virus (VEEV), pose a major global health challenge. Here, we report the synthesis and screening of a series of pyrrolo[2,3-b]pyridines targeting RSV, SARS-CoV-2 and/or VEEV. From this campaign, a series of lead compounds was generated that demonstrated antiviral activity in the low single-digit micromolar range against the various vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…A pyrrolo [2,3-b]pyridine analogue (compound 79, Figure 21) was identified as a potent anti-RSV agent (EC 50 = 0.19 μM) but with a low CC 50 value (2 μM). 173 Medicinal chemistry efforts focused on functionalizing the C-5 position and the alkynyl substituent, resulting in the identification of a series of derivatives with comparable EC 50 values to the starting hit but decreased cytotoxicity. Compound 80 (Figure 21) exhibited an EC 50 of 0.16 μM and a CC 50 > 50 μM and retained its anti-RSV activity (EC 50 = 0.59 μM) also when tested on different cells (A549).…”
Section: ■ Inhibitiors Of the Replication Complexmentioning
confidence: 99%
See 3 more Smart Citations
“…A pyrrolo [2,3-b]pyridine analogue (compound 79, Figure 21) was identified as a potent anti-RSV agent (EC 50 = 0.19 μM) but with a low CC 50 value (2 μM). 173 Medicinal chemistry efforts focused on functionalizing the C-5 position and the alkynyl substituent, resulting in the identification of a series of derivatives with comparable EC 50 values to the starting hit but decreased cytotoxicity. Compound 80 (Figure 21) exhibited an EC 50 of 0.16 μM and a CC 50 > 50 μM and retained its anti-RSV activity (EC 50 = 0.59 μM) also when tested on different cells (A549).…”
Section: ■ Inhibitiors Of the Replication Complexmentioning
confidence: 99%
“…This raised doubts about the MoA of this series of pyrrolo [2,3b]pyridine analogues. 173 In the same year, da Silva et al synthesized a series of triterpene derivatives that led to the identification of compound 81 (Figure 21), which is substituted with triazole and showed better anti-RSV activity (EC 50 = 0.05 μM, CPE on A549 cells infected with RSV A2 strain) than its close triterpene analogue, ursolic acid (which is approximately 3-fold less potent). In silico studies suggested that compound 75 may target inosine monophosphate dehydrogenase.…”
Section: ■ Inhibitiors Of the Replication Complexmentioning
confidence: 99%
See 2 more Smart Citations